Fungi as Nature’s Recyclers Optimizing Nutrient Dynamics in Agroecosystems - Nuri Salem Alnaass; Zuhra Bashir Khalifa Trabalsiy; Mabruka Hadya Abubaira; Najat Alarbi Alyaseer (African Journal of Advanced Pure and Applied Sciences, 2025)
Fungi are the hidden architects of agroecosystems, quietly driving essential nutrient cycles and maintaining soil health. Acting as nature’s recyclers, they break down organic matter, release vital nutrients, and form beneficial partnerships with plant roots through mycorrhizal networks. These processes not only enhance soil fertility but also significantly reduce reliance on synthetic fertilizers, promoting cost-effective and eco-friendly farming practices. Additionally, fungi play a crucial role in pathogen suppression by producing bioactive compounds, acting as natural biocontrol agents that protect crops from diseases and support higher yields. However, their functionality is influenced by environmental factors, including soil quality, temperature, and agricultural practices. Integrating fungi into modern farming systems requires a deep understanding of these dynamics to maximize their potential. Advances in biotechnology, such as fungal biofertilizers and inoculants, present new opportunities to optimize their use. Beyond improving productivity, fungi contribute to long-term ecological resilience by enhancing soil carbon storage, reducing greenhouse gas emissions, and supporting biodiversity. Harnessing the natural processes of fungi can revolutionize agriculture, offering a sustainable path forward. By balancing productivity with environmental preservation, fungi provide a key to meeting the growing demand for food in an era of climate challenges and resource constraints.